2005
DOI: 10.1364/ao.44.006496
|View full text |Cite
|
Sign up to set email alerts
|

Detection of sputtered metals with cavity ring-down spectroscopy

Abstract: We report on use of cavity ring-down spectroscopy (CRDS) as a means to detect and quantify ion sputtering of refractory metal species. CRDS measurements are made with a neodymium:YAG-pumped optical parametric oscillator laser system in the 375-400 nm region. CRDS sputtering measurements are presented for argon ions incident on iron, aluminum, molybdenum, and titanium. The measurements are based on absorption from fine-structure levels of the electronic ground-state multiplets. For each species, characteristic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 22 publications
0
43
0
Order By: Relevance
“…In these devices, sputter erosion of grids and other components places a fundamental limitation on lifetimes. Additionally, sputtered particles from within the * 8 , collector plates [9][10] , mass spectrometry 11 , quartz crystal microbalance [2][3][4][5][6][12][13][14] , Rutherford backscattering [15][16] , radioactive tracers 17 , and cavity ring-down spectroscopy 18 . In this contribution we present sputter measurements of BN obtained by both weight loss and the quartz crystal microbalance (QCM).…”
Section: Introductionmentioning
confidence: 99%
“…In these devices, sputter erosion of grids and other components places a fundamental limitation on lifetimes. Additionally, sputtered particles from within the * 8 , collector plates [9][10] , mass spectrometry 11 , quartz crystal microbalance [2][3][4][5][6][12][13][14] , Rutherford backscattering [15][16] , radioactive tracers 17 , and cavity ring-down spectroscopy 18 . In this contribution we present sputter measurements of BN obtained by both weight loss and the quartz crystal microbalance (QCM).…”
Section: Introductionmentioning
confidence: 99%
“…We ignore the upper state population of aluminum atoms, since Azer et al 16) showed that the population follows a Boltzmann distribution and its Boltzmann temperature is in the range of 300-2000 K. That is, we estimate the aluminum number density as the sum of two ground state populations ( …”
Section: Resultsmentioning
confidence: 99%
“…As reported in our earlier work, for the species and conditions of interest, the measured lower state population can be converted to overall species population through the energy level distributions 25 . We use equation (3) to determine the path-integrated concentration along a chord.…”
Section: Cavity Ring-down Spectroscopymentioning
confidence: 97%
“…Detailed reviews of the technique may be found in references 28 and 29. Our previous development of CRDS for sputter diagnostics has been previously described [24][25][26][27] . As shown in Fig.1, the absorbing sample is contained within a high-finesse optical cavity typically formed from two (or three) highreflectivity (R) mirrors with R ~0.9999.…”
Section: Cavity Ring-down Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation